Stereotactic Ablative Radiotherapy for Patients with Unresectable or Medically Inoperable Cholangiocarcinoma. Issue 3 (May 2017) - Liu, Ming-Yueh; Lo, Cheng-Hsiang; Lin, Chun-Shu; Chao, Hsing-Lung; Yang, Jen-Fu; Lin, Kuen-Tze; Fan, Chao-Yueh; Su, Yu-Fu; Huang, Wen-Yen
Purpose: The role of stereotactic ablative radiotherapy (SABR) in patients with unresectable or medically inoperable cholangiocarcinoma remains unclear. We examined the efficacy and safety of SABR in this group of patients. Methods: From January 2008 to December 2014, 15 patients with 17 lesions were included in this study. The lesions included 14 intrahepatic, 1 hilar, and 2 distal bile duct tumors. Three patients were classified as medically inoperable because of old age or multiple comorbidities. Tumors measured 0.8-13 cm (median, 3.6 cm). The median prescribed dose was 45 Gy delivered in 5 fractions over 5 consecutive days. Results: The median follow-up period for surviving patients was 29.9 months. Objective responses were observed for 10 of 17 tumors (58.8%), including 3 complete responses (17.6%). The median survival duration was 12.6 months, and the 1- and 2-year overall survival rates were 50.3% and 14.4%, respectively. The 1- and 2-year in-field failure-free rates were 61.5% and 30.8%, respectively. For patients with biologically effective doses (BEDs) exceeding 75 Gy10, the 1- and 2-year overall survival rates were 58.3% and 33.3%, respectively, compared to 20.0% and 0%, respectively for those with BEDs lower than 75 Gy10. Radiation-induced liver disease did not develop in any patient. Acute toxicities were generally mild and tolerable. Conclusions: Stereotactic ablative radiotherapy could be an alternative treatment for unresectable or medically inoperable cholangiocarcinoma. Further dose escalation may be considered to optimize local control.